The status of heavy metal levels in a Ramsar Site, Kuala Gula Bird Sanctuary: the impact of the anthropogenic inputs. - R.M., Lomoljo; Ismail, Ahmad; Yap, Chee Kong; Ismail, Abdul Rahim (Taylor & Francis, 2010)
Distributions of Cd, Cu, Pb, and Zn in the surface sediments from two sites of the Kuala Gula Bird Sanctuary, Malaysia were monitored for a period of 6 months from October 2006 to March 2007. In December 2006, the concentration of Zn in one location was significantly ( p50.05) higher (3.91.3 mgkg1) than the other metals at both sites, but in the oxidizable organic fraction it was highest at both sites during October; with mean concentrations of 18mg kg1 at both locations. In the acid-reducible fraction, high concentrations of Pb (2.3 mg kg1) were detected at station 2 in February 2007, being highest among all four metals at both stations. The acid-reducible fraction found in Pb ranged from 0.10% to 3.1% in both stations. Percentages ranging from 51% to 96% were observed for all four metals in the resistant fraction throughout the sampling period. These results indicate low contributions from anthropogenic sources. The findings constitute a baseline data archive for future reference.